Pengaruh Kecerdasan Interpersonal Tehadap Perilaku Bullying Pada Siswa Kelas V di SDN Teluk 02 - Imawati, Sri; Herawati, Sari (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine whether interpersonal intelligence has an effect on bullying behavior at SDN Teluk 02 and how much influence interpersonal intelligence has on bullying behavior at SDN Teluk 02. Because the phenomenon of bullying that often occurs in the school environment, especially verbal bullying, which students often do without they realize they are bullying most students when communicating with other students they do not understand very well how to choose good words and how to communicate well, therefore it is very important for educators to be aware of their role in increasing students' interpersonal intelligence from an early age so that later students are able to blend in with the surrounding community. This research is a quantitative research with survey method and using saturated sample technique. The data subjects of this study were students of class V A and class V B at SDN Teluk 02 as many as 65 students. The instrument used in this study was a questionnaire questionnaire. The results of data analysis show that interpersonal intelligence is very influential on bullying behavior because interpersonal intelligence emphasizes on a student by increasing students' interpersonal intelligence can reduce the impact of bullying behavior that occurs in the school environment as well as in the community as well as on social media.